Analisis Produktivitas Vibratory Roller Berdasarkan Variasi Passing pada Pekerjaan Trial Compaction di Proyek Reklamasi - Pramana, Aditya; Marantika, Lutfi; Sumarman, Sumarman (Jurnal Ragam Pengabdian, 2026)
Compaction in reclamation projects requires an effective method to achieve the specified soil density while maintaining optimum productivity. This study aimed to analyze the productivity of the Sakai SV512D vibratory roller under 18, 20, 24, and 26 compaction pass variations during the trial compaction process. A quantitative research approach was employed using trial compaction data, including equipment productivity, compaction time, coverage area, fuel consumption and cost, Sand Cone test results, and California Bearing Ratio (CBR) as a supporting parameter. The results indicate that increasing the number of compaction passes reduced equipment productivity, while compaction time, fuel consumption, and operating costs increased. The 18-pass variation achieved the highest productivity and the lowest operating cost, whereas the 24-pass variation provided the best balance between operational efficiency and compaction quality in accordance with the project’s technical specifications.